Reproductive Health Education: I am Healthy Physically and Spiritually Healthy Teenager - Lorensia Panselina Widowati; Eviyani Margaretha Manungkalit; Lucia Utami (LPPM UIKA Bogor, 2022)
Reproductive health is one of the Sustainable Development Goals that directly affect the health sector. Technological advances in the Industrial Revolution 4.0 ensure that information spreads widely and quickly via the Internet. Adolescents can easily obtain and retrieve information about sexuality from a variety of sources, but the truth and validity of the information must be credible. Misleading information provokes teens to conform to unhealthy sexual activities. Overall, unhealthy sexual activity can lead to the early onset of sexual activity and expose adolescents to high-risk sexual behavior. This study aimed to improve adolescents' knowledge of education about holistic reproductive health from different perspectives (medical, psychological and spiritual). This research uses qualitative research with descriptive methods using a Zoom meeting application with a total of 82 male and female participants. The implementation of the activity starts with a pre-test and ends with a post-test via Google Forms. As the study results show, the adolescents' knowledge about reproductive health education increased significantly by 18.5% in a comparison of the pretest and posttest. Reproductive health counseling has induced positive changes and attitudes in adolescents from different perspectives (medical, psychological and spiritual) regarding knowledge about reproductive health. Reproductive education counseling is expected to continue in each educational institute to improve adolescent reproductive health and protect adolescents from problematic sexual behavior.